1998
DOI: 10.1507/endocrj.45.261
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Gitelman's Syndrome with Chondrocalcinosis.

Abstract: Abstract. A 45-year-old Japanese woman, treated for Bartter's syndrome for 14 years, presented with complaints of numbness in her extremities and polyarthralgia.She was diagnosed to have Gitelman's syndrome with chondrocalcinosis, which were effectively treated with spironolactone and magnesium supplementation.Gitelman's syndrome is a primary renal tubular disorder characterized by hypomagnesemia and hypocalciuria with normal calcemia. The persistent hypomagnesemia is one of the causes of chondrocalcinosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…1, the radiographs of the knees demonstrated bilateral calcification in the cartilage, a picture compatible with the diagnosis of chondrocalcinosis, which has recently been reported in several cases of GS [9][10][11]. EEG, MRI and 99mTc-ECD SPECT studies of the brain showed no finding accounting for the loss of consciousness.…”
Section: Case Reportsupporting
confidence: 60%
“…1, the radiographs of the knees demonstrated bilateral calcification in the cartilage, a picture compatible with the diagnosis of chondrocalcinosis, which has recently been reported in several cases of GS [9][10][11]. EEG, MRI and 99mTc-ECD SPECT studies of the brain showed no finding accounting for the loss of consciousness.…”
Section: Case Reportsupporting
confidence: 60%
“…Remarkably, some patients are completely asymptomatic except for the appearance of chondrocalcinosis at adult age. 5,6 A minority of patients with GS have a mutation in the CLCNKB gene, coding for chloride channel subunit b (ClC-Kb). In most cases, GS results from loss-of-function mutations in the solute carrier family 12, member 3 (SLC12A3) gene, which consists of 26 exons and is located on the long arm of chromosome 16 (16q13).…”
Section: Introductionmentioning
confidence: 99%
“…La condrocalcinosi, come noto, è caratterizzata clinicamente da episodi di sinovite acuta o sinovite cronica, secondari al deposito di cristalli di pirofosfato diidrato di calcio a livello della cartilagine ialina e/o della fibrocartilagine (7). Diversi contributi in letteratura sottolineano l'associazione di SG e condrocalcinosi, considerata, quest'ultima, un tipico esempio di manifestazione secondaria ad ipomagnesemia (8)(9)(10)(11)(12)(13)(14). Descriviamo in seguito due casi di SG associati a condrocalcinosi, che illustrano due estremi dell'ampio ventaglio di presentazione di questa sindrome.…”
unclassified